SOCIETY TRANSFORMATION AND SOCIAL DEVELOPMENT THROUGH UNIVERSITY-COMMUNITY TRANSFORMATION CENTRE (UCTC) VIA UNIVERSITI TUN HUSSEIN ONN MALAYSIA EXPERIENCE - Omar, Abdul Razak; Tasmin, Rosmaini (Journal of Techno-Social, 2015)
Society transformation implies to various means in which globalising forces give impacts upon local communities and national societies with highly diverse historical backgrounds, social and economic patterns, political institutions and cultures. Hence, social development means a commitment that development processes need to benefit people, particularly but not only the poor, but also a recognition that people, and the way they interact in groups and society, and the norms that facilitates such interaction, shape development processes. Malaysia has a large base of middle income household segment. However, there are 94% working population which contributes to 32% on the Gross Domestic Product. In comparison to the countries at Western Europe, they attain a level of 65% working population that contributes to 51% GDP. This signifies that a majority of workforce contributes to the significant half of the wealth of the nations. Hence, it is important for Malaysia to attain these development levels through the leverage of information technology, the Internet and social media for the well-being of the community. University Community Transformation Centre (UCTC) is a mean to deliver more university intellectual and physical values to wider communities for their higher quality of living, activity outcome and income throughput. Academicians can also transfer and share their knowledge and expertise to community members in solving their constraints and problems. This paper highlights on UTHM community programmes that complement society daily problems and challenges, hence uplifting the well-being of community and business alike.